Lactiplantibacillus plantarum YZX28 alleviated intestinal barrier dysfunction induced by enterotoxigenic Escherichia coli via inhibiting its virulence factor production. (December 2022) - Peng, Bo; Cui, Qingyu; Ma, Chao; Yi, Huaxi; Gong, Pimin; Lin, Kai; Liu, Tongjie; Zhang, Lanwei
Abstract: Probiotics are emerging as a promising approach to treating foodborne infections or gastrointestinal diseases. This study aimed to explore the protective effect of Lactiplantibacillus plantarum YZX28 (YZX28) on intestinal barrier dysfunction induced by enterotoxigenic Escherichia coli K80 (ETEC K80). Caco-2 cells were used for in vitro co-culture experiments of enterotoxin-producing ETEC K80 and YZX28. The barrier permeability (higher phenol red flux and decreased TEER) and levels of pro-inflammatory cytokines TNF-α and IL-8 increased by ETEC K 80 were attenuated by YZX28, and the mRNA levels of tight junctions, including ZO-1, occludin, claudin-1, and cingulin were significantly increased by YZX28 intervention. The redistribution of ZO-1, claudin-1, and actin fibers in Caco-2 cells induced by ETEC K 80 was restored. Furthermore, YZX28 could effectively reduce the adhesion level of ETEC to Caco-2 cells, alleviate the decrease of cell viability induced by ETEC, and inhibit the expression of ETEC virulence factors, including enterotoxin STa (est-A), STb (est-B), LT (elt) as well as fimbria adhesin FaeG and reduced the corresponding cAMP, cGMP, and CEACAM6 levels. This strain may be a potential therapeutic agent for treating intestinal-related problems caused by the intestinal pathogen ETEC. Highlights: Lactiplantibacillus plantarum YZX28 decreased the adhesion of ETEC to Caco-2. Lactiplantibacillus plantarum YZX28 protected intestinal barrier from ETEC injury . Lactiplantibacillus plantarum YZX28 inhibited virulence factor expressions in ETEC.